TEORIA MARXISTA DO VALOR: UMA INTRODUÇÃO - Saad Filho, Alfredo (Análise Econômica, 2009)
This article provides an elementary introduction to the basic concepts of the Marxian theory of value and exploitation. The paper explores the concepts of commodity use value and exchange value, concrete and abstract labour, and the relationship between value and money it also explains the nature of the capital relation, the process of exploitation of the wage workers and the extraction of surplus value, and the process of competition. The article concludes with an analysis of the most important contradictions of capitalism.